2010
DOI: 10.1007/s12161-010-9172-2
|View full text |Cite
|
Sign up to set email alerts
|

Use of Multivariate Analysis Techniques for Evaluation of Analytical Data—Determination of the Mineral Composition of Cabbage (Brassica oleracea)

Abstract: Cabbage (Brassica oleracea) is a vegetable food that is found in red and white varieties, and it has been consumed worldwide as raw or cooked. In this paper, the mineral composition of cabbage collected in 24 Brazilian cities was determined and the results were evaluated using multivariate analysis. The samples were digested using nitric acid and hydrogen peroxide and were analyzed using inductively coupled plasma optical emission spectrometry. The accuracy of the method was confirmed by analysis of a certifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…Both (PCA and HCA) are either classified as exploratory or unsupervised, since no information regarding the identity of the samples is considered. Anunciação et al (2011), determined and evaluated, through multivariate analysis, the mineral composition of red and white cabbage and found higher mean concentrations of K, P and Ca in these samples. Furthermore, PCA did not show difference between the mineral compositions of red and white species of cabbage (Anunciação et al 2011).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both (PCA and HCA) are either classified as exploratory or unsupervised, since no information regarding the identity of the samples is considered. Anunciação et al (2011), determined and evaluated, through multivariate analysis, the mineral composition of red and white cabbage and found higher mean concentrations of K, P and Ca in these samples. Furthermore, PCA did not show difference between the mineral compositions of red and white species of cabbage (Anunciação et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Anunciação et al (2011), determined and evaluated, through multivariate analysis, the mineral composition of red and white cabbage and found higher mean concentrations of K, P and Ca in these samples. Furthermore, PCA did not show difference between the mineral compositions of red and white species of cabbage (Anunciação et al 2011). Dos Santos et al (2013b, determined the mineral content (Ca, Cu, K, Mg, Na, P and Zn) of raw and cooked okra of conventional and organic cultivars and observed that raw samples had the highest concentrations, indicating a loss of nutrients during cooking.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, juice samples were digested on a digestion block based on the methodology established by Anunciação et al 27 5 mL of each sample were added to a glass vessel and then it was added 10 mL of concentrated nitric acid (14.4 mol L ) hydrogen peroxide. The digestion block temperature was adjusted to 140 °C and the samples were digested for 90 min.…”
Section: Total Phosphorus Determinationmentioning
confidence: 99%
“…However, others nutrients like calcium, magnesium, potassium, sodium that also are necessary for life, but are present in higher quantities. Research carried from plant sources of conventional and unconventional demonstrate the existence of significant levels of these nutrients, contemplating the needs of recommended daily intakes [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%